PENGENALAN GREEN BEHAVIOUR MELALUI ECOLITERACY PADA SISWA MI - Maghfiroh Liulinnuha; Salamatun Umma (PREMIERE : Journal of Islamic Elementary Education, 2022)
This study aims to inform ecoliteracy is an important effort to build green behavior. The environment is the main pillar for all life including human life. Someone who has realized the importance of the environment means that he has entered the level of ecoliteracy. Ecoliteracy is an awareness of someone who has realized how important it is to protect and care for the environment. Green behavior is the behavior of protecting and maintaining the environment. Environmental education needs to be given to students, even from an early age, so that environmental balance is maintained. This study aims to introduce ecoliteracy through green behavior activities to MI students. Three people who play an important role in this are parents, teachers and students themselves. The introduction of green behavior in children aged MI can be started by habituation of exemplary attitudes and daily habits. The introduction of green behavior through ecoliteracy for children can also be done using the storytelling method, besides telling stories, they can also do field trips to provide awareness of how important the environment is for them. This study uses qualitative research with literature study methods or library research by collecting research data from relevant journal literature sources in the last 10 years.